Analgesic Activity of Isatin Derivatives - A. Khan, Suroor; A. Siddiqui, Anees; Bhatt, Shibeer (Asian Journal of Chemistry, 2010)
Schiff bases of isatin are prepared and characterized on the basis of IR and NMR spectral data. The final compounds are evaluated for analgesic activity.